Perceptions and Early Outcomes of the Acuity Circles Allocation Policy Among Liver Transplant Centers in the United States. Issue 1 (12th December 2022) - Pawlak, Natalie; Song, Cherilyn; Alvi, Saba; Schuster, Kimberly; Segalini, Nicole; Kwon, Yong K.; Akoad, Mohamed E.; Rauf, M. Ameen; Mulligan, David; Aziz, Hassan
Abstract : Background: Recently, a new liver allocation policy called the acuity circles (AC) framework was implemented to decrease geographic disparities in transplant metrics across donor service areas. Early analyses have examined the changes in outcomes because of the AC policy. However, perceptions among transplant surgeons and staff regarding the new policy remain unknown. Methods: A 28-item survey was sent to division chiefs and surgical directors of liver transplantation across the United States. Questions assessed the respondents' perceptions regarding center-level metrics and staff satisfaction. We used Organ Procurement and Transplantation Network data to study differences in allocation between the pre-AC implementation period (2019) and the post-AC implementation period (2020–2021). Results: A total of 40 participants completed this ongoing survey study. Most responses were from region 8 (13%), region 10 (15%), and region 11 (13%). Sixty-three percent of respondents stated that the wait time for a suitable offer for recipients with model of end-stage liver disease score <30 has decreased, whereas 50% stated that wait time for a suitable offer for recipients with model of end-stage liver disease score >30 has increased. However, most respondents (75%) felt that the average cost per transplant had increased and that the rate of surgical complications and 1-y graft survival had remained the same. In most states, an observable decrease in in-state liver transplantations occurred each year between 2019 and 2021. In addition, most allocation regions reported an increase in donations after circulatory deaths between 2019 and 2021. Conclusions: Perceptions of the new AC policy among liver transplant surgeons in the United States remain mixed, highlighting the potential strengths and concerns regarding its future impact. Further studies should assess the effects of the AC policy on clinical outcomes and liver transplantation access.